2017
DOI: 10.1093/mnras/stx319
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the most massive black holes at high-z: BlueTides and the next quasar frontier

Abstract: The growth of the most massive black holes in the early universe, consistent with the detection of highly luminous quasars at z > 6 implies sustained, critical accretion of material to grow and power them. Given a black hole seed scenario, it is still uncertain which conditions in the early Universe allow the fastest black hole growth. Large scale hydrodynamical cosmological simulations of structure formation allow us to explore the conditions conducive to the growth of the earliest supermassive black holes. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 38 publications
7
91
1
Order By: Relevance
“…BLUETIDES also consistently predicted the properties of GN-z11 (Oesch et al 2016) which is the farthest galaxy observed to date (Waters et al 2016a). BLUETIDES forecasts for the upcoming WFIRST satellite have been made by Waters et al (2016b) and results look promising with about 10 ume of BLUETIDES it has also been possible to study the formation of the first quasars, supermassive black holes (Di Matteo et al 2017).…”
Section: Introductionmentioning
confidence: 54%
“…BLUETIDES also consistently predicted the properties of GN-z11 (Oesch et al 2016) which is the farthest galaxy observed to date (Waters et al 2016a). BLUETIDES forecasts for the upcoming WFIRST satellite have been made by Waters et al (2016b) and results look promising with about 10 ume of BLUETIDES it has also been possible to study the formation of the first quasars, supermassive black holes (Di Matteo et al 2017).…”
Section: Introductionmentioning
confidence: 54%
“…Our data provide a good test for large cosmological simulations that allow the study and prediction of the observational properties of the first galaxies and supermassive black holes in the universe (e.g., Feng et al 2016;Lupi et al 2019). For example, the brightest quasar in the BlueTides simulation has a similar luminosity and black hole mass at z = 7.54 to J1342+0928 (Di Matteo et al 2017;Tenneti et al 2019), but some of the predictions on the host galaxy of the simulated quasar are different from our findings. Ni et al (2018) find that the simulated BlueTides z = 7.54 quasar produces gas outflows reaching thousands of km s −1 with respect to the systemic redshift, similar to what reported in a quasar at z = 6.4 (Cicone et al 2015).…”
Section: Comparison To Simulationsmentioning
confidence: 81%
“…In the recent decade, large-scale cosmological simulations studying galaxy formation and evolution have been carried out intensively, e.g., FIRE (e.g., Hopkins et al 2014), and Illustris (e.g., Vogelsberger et al 2014) simulation. Some simulation studies (e.g., Habouzit et al 2017;Di Matteo et al 2017) focused on the early epoch of the Universe and investigated the relationships between growth of high-z BHs and the properties of their host halos. As a sub-grid model to characterize rapid growth of BHs, the transition conditions would be applicable for those cosmological simulations which do not resolve the Bondi radius of the BHs.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%